This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Barkley, Thane – Exam 2 – Due: Oct 31 2007, 1:00 am – Inst: Louiza Fouli 1 This printout should have 20 questions. Multiplechoice questions may continue on the next column or page – find all choices before answering. The due time is Central time. 001 (part 1 of 1) 10 points Find f ( x ) when f ( x ) = ‡ x 1 x + 1 · 2 . 1. f ( x ) = 6( x + 1) ( x 1) 3 2. f ( x ) = 4( x 2) ( x + 1) 3 3. f ( x ) = 6( x 2) ( x + 1) 3 4. f ( x ) = 4( x + 1) ( x 1) 3 5. f ( x ) = 4( x 1) ( x + 1) 3 correct 6. f ( x ) = 6( x + 2) ( x 1) 3 Explanation: By the Chain and Quotient Rules, f ( x ) = 2 ‡ x 1 x + 1 · ( x + 1) ( x 1) ( x + 1) 2 . Consequently, f ( x ) = 4( x 1) ( x + 1) 3 . keywords: derivative, quotient rule, chain rule 002 (part 1 of 1) 10 points Determine f ( x ) when f ( x ) = 2 √ x sin √ x . 1. f ( x ) = 2 n cos √ x √ x sin √ x o 2. f ( x ) = 1 2 n cos √ x √ x sin √ x o 3. f ( x ) = cos √ x √ x sin √ x 4. f ( x ) = 1 2 n sin √ x √ x + cos √ x o 5. f ( x ) = 2 n sin √ x √ x + cos √ x o 6. f ( x ) = sin √ x √ x + cos √ x correct Explanation: By the Chain and Product Rules, f ( x ) = 2 2 √ x sin √ x + 2 √ x 2 √ x cos √ x . Consequently, f ( x ) = sin √ x √ x + cos √ x . keywords: chain rule, product rule, trig func tion 003 (part 1 of 1) 10 points Find the second derivative of f when f ( x ) = cos2 x + 3sin 2 x . 1. f 00 ( x ) = cos2 x 2. f 00 ( x ) = cos2 x 3. f 00 ( x ) = 2cos2 x 4. f 00 ( x ) = sin2 x 5. f 00 ( x ) = 2cos2 x correct Barkley, Thane – Exam 2 – Due: Oct 31 2007, 1:00 am – Inst: Louiza Fouli 2 6. f 00 ( x ) = 2sin2 x Explanation: Differentiating once we see that f ( x ) = 2sin2 x + 6sin x cos x . Now 2sin x cos x = sin2 x , so f ( x ) = sin2 x . Consequently, by differentiating once again we obtain f 00 ( x ) = 2cos2 x . keywords: second derivative, trig function 004 (part 1 of 1) 10 points Determine the third derivative, f 000 ( x ), of f when f ( x ) = √ 2 x + 1 . 1. f 000 ( x ) = (2 x + 1) 3 / 2 2. f 000 ( x ) = 3(2 x + 1) 5 / 2 3. f 000 ( x ) = (2 x + 1) 5 / 2 4. f 000 ( x ) = 3(2 x + 1) 5 / 2 correct 5. f 000 ( x ) = 3(2 x + 1) 3 / 2 6. f 000 ( x ) = (2 x + 1) 3 / 2 Explanation: TousetheChainRulesuccessively it’smore convenient to write f ( x ) = √ 2 x + 1 = (2 x + 1) 1 / 2 . For then f ( x ) = 1 2 · 2 · (2 x + 1) 1 / 2 = (2 x + 1) 1 / 2 , while f 00 ( x ) = 1 2 · 2 · (2 x + 1) 3 / 2 = (2 x + 1) 3 / 2 , and f 000 ( x ) = 3 2 · 2 · (2 x + 1) 5 / 2 . Consequently, f 000 ( x ) = 3(2 x + 1) 5 / 2 . keywords: third derivative, chain rule 005 (part 1 of 1) 10 points Find dy/dx when 5 x 2 + 3 y 2 = 9 . 1. dy dx = 5 x 3 y 2. dy dx = 3 xy 3....
View
Full
Document
This test prep was uploaded on 04/16/2008 for the course M 408k taught by Professor Schultz during the Fall '08 term at University of Texas at Austin.
 Fall '08
 schultz
 Calculus

Click to edit the document details